Pelvic Floor Muscle Training for Stress Urinary Incontinence, with and without Biofeedback: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Leonardo, Kevin (Bentham Science Publishers, 2022)
Background: Pelvic floor muscle training (PFMT) with biofeedback is used widely in treating patients with stress urinary incontinence (SUI), despite unclear evidence. We conducted a meta-analysis of the literature to evaluate the efficacy of treatment after PFMT with and without biofeedback in SUI patients. Methods: We searched PubMed, CENTRAL, CINAHL, and Science Direct for randomized controlled trials (RCTs) of PFMT with and without biofeedback for SUI. RCTs were screened with our eligibility criteria, and the risk of bias was assessed according to the Cochrane risk of bias tool for randomized trials. The outcomes analyzed were pelvic floor muscle (PFM) strength, incontinence episode, daytime micturition, and nighttime micturition, all measured as mean difference (MD) with 95 confidence intervals (CIs). Heterogeneity and publication bias were analyzed using the I2 test and a funnel plot, respectively. Results and Discussion: Pooled analysis of five RCTs involving 207 patients showed that the difference in PFM strength and nighttime micturition between both groups was significant. Although PFM strength improvement favors biofeedback-assisted pelvic floor muscle training (BPFMT) (MD 12.29, 95 CI 2.33, 22.25, p=0.02), in contrast, nighttime micturition was significantly reduced in the PFMT group (MD 0.44, 95 CI 0.12 to 0.77, p=0.007). Differences in incontinence episode and daytime micturition were not significant (MD-0.08, 95 CI-0.57 to 0.41, p=0.75 and MD 0.55, 95 CI-0.36 to 1.46, p=0.24, respectively). Conclusion: This meta-analysis showed that BPFMT had a better outcome in improving PFM strength, while nighttime micturition was, on the contrary, better in PFMT only. Meanwhile, no significant differences in incontinence episodes and daytime micturition outcomes were noted between both groups. With the present evidence, routine use of BPFMT is not necessary for current clinical practice. © 2022 Leonardo et al.